JESD 2019
DOI: 10.7176/jesd/10-16-19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rainfall on Agricultural Growth in Thailand: Evidence in Farming and Fishing Activities

Abstract: Rainfall is related to economic growth. This is especially true for the agricultural sector which is a key food source. Rainfall has beneficial impacts in both arid and poor regions. Thailand, as an upper middle-income country according to the World Bank, has a tropical climate although rainfall varies between each region. Precipitation in the northern and northeastern regions is low while the southern region, as a narrow strip of land running northsouth bordering the Andaman Sea to the West and the Gulf of Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…Although their 'R' values were more than 1 (Table 2), we considered revising them given that dissociation had been explicitly found to exist between the statistical values and their ascriptions. Most participants solidly indicated that the existence of water sources like rainfall and surface water (irrigation) is the foundation of agriculture, especially for organic rice farming (Sangkhaphan & Shu, 2019). This is because those water sources are not only essential for nourishing rice production, but they are also important in suppressing weeds and in enhancing soil structure by allowing for better nutrient retentive abilities (Polthanee, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although their 'R' values were more than 1 (Table 2), we considered revising them given that dissociation had been explicitly found to exist between the statistical values and their ascriptions. Most participants solidly indicated that the existence of water sources like rainfall and surface water (irrigation) is the foundation of agriculture, especially for organic rice farming (Sangkhaphan & Shu, 2019). This is because those water sources are not only essential for nourishing rice production, but they are also important in suppressing weeds and in enhancing soil structure by allowing for better nutrient retentive abilities (Polthanee, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the role of rainfall was likely to be more significant in the case of those participants, who were growing organic rice in the highlands, where irrigation is scarce or absent (Panomsak & Sakdapolrak, 2012) because rainfall may be the single source, which maintains their crops (Olayide et al, 2016). Even underground water sources on the land, such as wells and ponds, which are man-made attempts at construction, are likely to malfunction if the reinforcement of rainfall is absent (Sangkhaphan & Shu, 2019). Therefore, these two indicators were recommended to amalgamate the process and make it more holistic and precise so that resilience can be monitored.…”
Section: Resultsmentioning
confidence: 99%
“…mengandalkan iklim untuk aktivitasnya Sangkhaphan & Shu (2019). Hal ini menegaskan pernyataan (Lee, Villaruel, & Gaspar, 2016) bahwa perubahan iklim berdampak pada seluruh sektor perekonomian negara seperti sektor pertanian, industri, dan investasi.…”
unclassified